Pemanfaatan Digital Marketing Pemasaran Hasil Pertanian Berbasis Online Pada Kelompok Tani Sapto Gati Desa Pojok Garum Kabupaten Blitar - Indyah Hartami Santi; Indria Guntarayana (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Technological developments require every business actor to be able to utilize information technology in marketing their products, as well as the Sapto Gati farmer group. The marketing system that has been carried out so far is using conventional marketing, direct buying and selling is limited to friends, close friends and family. Along with the development of information technology, this farmer group seeks new breakthroughs by changing the conventional marketing system by utilizing digital marketing. The purpose of this community service activity is to provide ongoing assistance, especially in the marketing of products and processed products of the Sapto Gati farmer group. The strategy used is to conduct surveys and interviews and then carry out a needs analysis, system design and implementation of the online marketing application system. After the marketing application is complete, then socialization is carried out to get responses, feedback and input for the perfection of the application being built. The result of this activity is that the SIANTAR application is an online marketing system (digital marketing) with the hope that the application can help farmer groups in marketing their agricultural products online, and expects to be developed sustainably according to the needs of farmer groups.